ANALISIS PERBANDINGAN KERUSAKAN JALAN RAYA DENGAN METODE PAVEMENT CONDITION INDEX DAN BINA MARGA - Yani Nabila, Fitri; Dewi, Selpa; Ishak, Ishak (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Highways are infrastructure built to facilitate mobility and accessibility of socio-economic activities, both between cities, villages and other areas. Good road conditions will facilitate community mobility activities, if there is damage to the road, community activities will be hampered and accidents can occur. The aim of this research is to determine the types of damage and pavement index values for the Bukittinggi-Padang Highway, Pasar Koto Baru, X Koto District, Tanah Datar Regency, so that it can compare the condition values of these road sections based on two predetermined methods. The methods used are the PCI (Pavement Condition Index) method and the Bina Marga method. The assessment of road conditions using the PCI method is ranked from 0-100, while the Bina Marga method is based on the order of road priority with a value range of 0-7. The types of damage found on the 2.0 km long Bukittinggi-Padang Highway, Pasar Koto Baru District Using the PCI method, the average value obtained is 77.90, which is very good road condition. In the Bina Marga method, a priority order value of 9.30 is obtained, meaning the road is under routine maintenance. After comparing the results of research on the condition of the Bukittinggi-Padang Highway, Pasar Koto Baru, worsening road conditions.Keywords: Road damage analysis; PCI method; Bina Marga method; Bukittinggi-Padang Highway Pasar Koto Baru X Koto District, Tanah Datar Regency.